1997
DOI: 10.3354/ame012223
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of annual variation in heterotrophic bacterial production in the Schelde estuary (SW Netherlands)

Abstract: Heterotrophic bacter~oplankton production (3H-thymidine incorporation rate) and abundance in the surface water of the Schelde estuary (The Netherlands) were studied during an annual cycle in 1991 along the salinity gradient ( 0 8 to 33 psu) Bacterial production and numbers increased from the lower to the uppel estuary This spatial varlabil~ty of bacterial production was positively coilelated wlth concentrations of dissolved and particulate organic carbon and negatively correlated with the oxygen concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 24 publications
9
32
2
Order By: Relevance
“…They are in the same range observed during the summer monsoon months (June --September) in other areas of open Arabian Sea (Goosen et al 1997, Wiebinga et al 1997. Bacterial production also agreed with ranges reported by Goosen et al (1997) and Wiebinga et al (1997) during southwest monsoon. This clearly suggests that a large area in the Arabian Sea experiences low abundance and production of bacteria during the summer monsoon.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They are in the same range observed during the summer monsoon months (June --September) in other areas of open Arabian Sea (Goosen et al 1997, Wiebinga et al 1997. Bacterial production also agreed with ranges reported by Goosen et al (1997) and Wiebinga et al (1997) during southwest monsoon. This clearly suggests that a large area in the Arabian Sea experiences low abundance and production of bacteria during the summer monsoon.…”
Section: Discussionsupporting
confidence: 76%
“…Under the Joint Global Ocean Flux Study (JGOFS) programmes, there have been a number of recent studies on the abundance (and production) of bacteria in the Arabian Sea (Burkill et al 1993;Ducklow 1993;Wiebinga 1994;Ramaiah et al 1996;Goosen et al 1997;Veldhuis et al 1997;Wiebinga et al 1997;Campbell et al 1998). Seasonal variations are clearly seen with higher abundance and production rates during spring and fall inter-monsoons (Ramaiah et al 1996;Campbell et al 1998;Pomroy and Joint 1999).…”
Section: Introductionmentioning
confidence: 99%
“…6C,D). Such observations are in resulting in compartmentalization of surface and botagreement with previous studies, such as Lovejoy et al tom waters in relation to ecological parameters such as (1996) and Goosen et al (1997) who demonstrated temtemperature, DO, nutritional contents, and bacterial perature as one of the most influential environmental abundance (Figs. 1 to 4).…”
Section: Discussioncontrasting
confidence: 52%
“…The lack of interannual and seasonal correspondence between BP and phytoplankton productivity and biomass was not unexpected and has been seen for some other estuarine systems (Findlay et al 1991, Ducklow & Shiah 1993, Staroscik & Smith 2004. Others report a close coupling between BP and phytoplankton parameters (Cole et al 1988, Hoch & Kirchman 1993, Goosen et al 1997, although the number of studies with multiyear coverage is limited.…”
Section: Discussionmentioning
confidence: 99%